Geologic Trends in Shear Strength Properties Inferred Through Three‐Dimensional Back Analysis of Landslide Inventories. Issue 9 (14th September 2020) - Bunn, Michael; Leshchinsky, Ben; Olsen, Michael J.
Abstract: Landslides occur in a variety of forms that are a function of climactic setting, tectonic setting, geomorphic and geologic setting, and the shear strength of soil and rock. While major advances in characterizing the spatial influence of these settings on landslide activity have occurred in recent years, there has been limited progress on understanding spatial trends in shear strength properties and their influence on landslide activity. Herein, we propose a regional‐scale forensic methodology to establish first‐order estimates of landslide shear strength. This approach is performed using (1) interpolation of rupture surface geometry and (2) three‐dimensional slope stability analysis. Thereafter, distributions of back‐analyzed shear strengths of landslide inventories are used to demonstrate that distinctly different trends are observed when comparing geologic units and landslide type. It is shown that there is generally an inverse correlation between landslide volume and friction angle, suggesting that larger earthflows tend to be in a residual state of shear, while smaller deep‐seated failures tend to occur in stronger, possibly cemented materials. Significant uncertainty lies in characterization of hydrological conditions; nonetheless, upper and lower bounds of groundwater conditions still reflect significant differences in inferred regional trends in shear strength properties between geologic settings. A comparison of three‐dimensional forensic back analyses to conventional, infinite slope conditions often used in susceptibility analyses suggests that conventional approaches may significantly overestimate landslide shear strengths at a regional scale. Key Points: Landslide inventories are used to characterize trends in shear strengths at a regional scale through three‐dimensional stability analyses There is an inverse correlation between landslide volume and friction angle, potentially reflecting landslide mechanism Three‐dimensional forensic analyses suggest that infinite slope stability analyses overestimate shear strengths at a regional scale